Parenthetical niching: A third‐factor phonosyntactic analysis. (8th January 2022) - McInnerney, Andrew
Abstract: In this article, I develop a theory of how a syntactically unintegrated parenthetical is integrated with its host at the sensorimotor interface. First, I observe that the niches open to parentheticals, traditionally described in syntactic terms, are more accurately described in the terms of prosodic‐hierarchy theory. In particular, I show that a niche corresponds to a phonological‐phrase boundary. I then argue that this follows if a parenthetical is constructed in a separate syntactic workspace and is integrated with its host at the sensorimotor interface (without ever being integrated in narrow syntax) in a manner that is constrained by (i) certain properties of the syntactic workspace, (ii) the No‐Tampering Condition, and (iii) certain properties of the syntax–phonology mapping.